2013
DOI: 10.1155/2013/638057
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Ethanol and Fomepizole Use in Toxic Alcohol Ingestions

Abstract: Objectives. The optimal antidote for the treatment of ethylene glycol or methanol intoxication is not known. The objective of this systematic review is to describe all available data on the use of ethanol and fomepizole for methanol and ethylene glycol intoxication. Data Source. A systematic search of MEDLINE and EMBASE was conducted. Study Selection. Published studies involving the use of ethanol or fomepizole, or both, in adults who presented within 72 hours of toxic alcohol ingestion were included. Our sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 133 publications
3
26
1
5
Order By: Relevance
“…This allowed for management of the most severely poisoned patients through the most critical phases, including the dialysis sessions where ethanol dosing is especially difficult 37 . The relatively higher prevalence of visual and CNS sequelae in our study compared to the literature, where 18-30% have been reported 26,36 , can be explained as an underestimation of the long-term impairment due to the absence of follow-up prospective studies in patients who survived poisonings with complete ocular and neurological examinations, and CT/MRI of brain to detect the subclinical damage to the basal ganglia.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This allowed for management of the most severely poisoned patients through the most critical phases, including the dialysis sessions where ethanol dosing is especially difficult 37 . The relatively higher prevalence of visual and CNS sequelae in our study compared to the literature, where 18-30% have been reported 26,36 , can be explained as an underestimation of the long-term impairment due to the absence of follow-up prospective studies in patients who survived poisonings with complete ocular and neurological examinations, and CT/MRI of brain to detect the subclinical damage to the basal ganglia.…”
Section: Discussioncontrasting
confidence: 80%
“…Fomepizole administration as a first-choice antidote is a well-established treatment in patients with acute methanol poisoning 14,34 . However, the relative efficacy of fomepizole is still under discussion 35,36 . In our study, fomepizole was administered to patients hospitalized during the outbreak of mass methanol poisonings in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both ethanol and fomepizole are effective, fomepizole is the preferred antidote for methanol poisoning 2. According to a systematic review,3 the mortality in patients treated with ethanol was 21.8% and in those administered fomepizole, was 17.1%. The mortality in patients treated with both antidotes was 5.5% 3.…”
Section: Introductionmentioning
confidence: 99%
“…37 En la inhibición de la alcohol deshidrogenasa es de elección el fomepizol sobre el etanol, debido a que el primero no induce embriaguez, hipoglucemia o irritación gástrica, que representan problemas frecuentes con el empleo de etanol (la irritación gástrica se presenta con la administración enteral de etanol). 40,41 El fomepizol se indica con una dosis inicial de 15 mg/kg, seguido de dosis de mantenimiento de 10 mg/ kg cada 12 horas, reajustándolas a cada 4 horas en caso de que se requiera hemodiálisis. Una alternativa eficaz es el etanol por vía enteral o intravenosa, con una dosis inicial de 800 mg/kg de peso para administrar en 20 minutos, seguida de dosis de mantenimiento de 80 a 150 mg/kg por hora, manteniendo al paciente en un estado leve de embriaguez (100 a 150 mg/dL en suero); [37][38][39] en este caso, si se inicia terapia con hemodiáli-sis el aporte también deberá ajustarse de 250 a 350 mg/kg por hora.…”
Section: Alcoholesunclassified